2002
DOI: 10.1002/ab.80006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of religiosity and ethnic origin on direct and indirect aggression among males and females: Some Israeli findings

Abstract: Israeli society is characterized by significant internal divisions. Two of the most salient of these divisions within the Jewish population relate to (1) religiosity (religious vs. secular Jews) and (2) ethnic origin (Eastern [Asian and North African] vs. Western [European and American]). The aim of this study was to assess the effects of these social divisions on aggressive behavior and victimization to aggression among Israeli children. Three types of aggressive behavior (physical, verbal, and indirect) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…The participants with the highest levels of appetitive aggression were those who had high scores of negative religious coping and low scores of positive religious coping. That religiosity has a positive impact on aggression was stressed by Landau et al (2002), who reported that secular respondents scored higher on aggressive behavior than their religious counterparts. There are several possible explanations for this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants with the highest levels of appetitive aggression were those who had high scores of negative religious coping and low scores of positive religious coping. That religiosity has a positive impact on aggression was stressed by Landau et al (2002), who reported that secular respondents scored higher on aggressive behavior than their religious counterparts. There are several possible explanations for this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, adherence to religious principles might be expected to be negatively related to aggression and violent behavior. A large number of studies have found that religiosity might inhibit aggressive behavior (Hardy, Walker, Rackham, & Olsen, 2012;Landau, Björkqvist, Lagerspetz, Österman, & Gideon, 2002;Leach, Berman, & Eubanks, 2008). However, the association between appetitive aggression and religiosity has received no attention to date.…”
mentioning
confidence: 99%
“…Other studies indicated that the relationship between age and relational aggression is moderated by sex (Cairns et al 1989;Owens and MacMullin 1995;Peets and Kikas 2006). Finally, several additional cross-sectional studies that examined a wider age range demonstrated a curvilinear relationship where relational aggression peaked in early adolescence before declining in later adolescence (Bjorkqvist et al 1992a;Landau et al 2002;Tiet et al 2001). To date, only a handful of longitudinal studies have examined the effects of development on relational aggression, and while they have yielded only limited support for Bjorkqvist et al's (1992a) theory, they have involved limited age ranges and/or problematic methodologies (e.g., maternal report) (Cillessen and Mayeux 2004;Vaillancourt et al 2003).…”
Section: Age and Relational Aggression Revisited From A Social Networmentioning
confidence: 93%
“…Indeed, it is likely that changes in network features affect the display of relational aggression across developmental periods. Here, attention is given to network features in early adolescence, as there is evidence that relationally aggressive behavior diversifies and potentially peaks during this developmental period (Bjorkqvist et al 1992a;Landau et al 2002;Tiet et al 2001).…”
Section: Network Features Of Early Adolescentsmentioning
confidence: 96%
“…The Direct and Indirect Aggression Scale (DIAS, Björkqvist et al 1992) which was translated into Hebrew by Landau et al (2002) was used to measure student's violent behavior in school. Three different forms of violence were assessed: physical aggression such as kicking and hitting others (7 items), verbal aggression such as teasing or insulting others (5 items) and indirect aggression such as ignoring others or saying bad things behind other's backs (12 items).…”
Section: Violence In Schoolsmentioning
confidence: 99%